2016
DOI: 10.3892/mmr.2016.5759
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs involved in Parkinson's disease: A systematic review

Abstract: The aim of the present study was to determine the expression of blood microRNAs (miRNAs) involved in PD in humans. For this purpose the following electronic databases were selected: MEDLINE by Pubmed, Scopus and Web of Science. The search strategy included the proposed descriptors in the Medical Subject Headings. There were no restrictions with respect to the language of the publication. In the study selection two independent reviewers initially evaluated studies that were identified by the search strategy acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Along these lines, qualitative reviews on the role of miRNAs in PD are largely based on a (subjective) selection of the literature that does not hold up to systematic meta‐analyses. For instance, in five recent articles reviewing the role of miRNAs in PD based on human expression or on experimental data (including one systematic review), 190 miRNAs were highlighted as being potentially relevant in PD (Supplementary Table 8). Of these, expression data were lacking or sparse for 113 (59%), that is, they could not be meta‐analyzed here.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, qualitative reviews on the role of miRNAs in PD are largely based on a (subjective) selection of the literature that does not hold up to systematic meta‐analyses. For instance, in five recent articles reviewing the role of miRNAs in PD based on human expression or on experimental data (including one systematic review), 190 miRNAs were highlighted as being potentially relevant in PD (Supplementary Table 8). Of these, expression data were lacking or sparse for 113 (59%), that is, they could not be meta‐analyzed here.…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, qualitative reviews on the role of miRNAs in PD are largely based on a (subjective) selection of the literature that does not hold up to systematic meta-analyses. For instance, in five recent articles reviewing the role of miRNAs in PD based on human expression or on experimental data (7,24-27) (including one systematic review (27)), 190 miRNAs were highlighted as being potentially relevant in PD (Supplementary 8). Of these, expression data were lacking or sparse for 113 (59%), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In murine embryonic brain cortices during hypoxia-induced neuronal apoptosis, the miR-23b-27b cluster was also found to be downregulated depending on the transcription factor c-Myc (Chen et al, 2015 ). Taking into account that a number of recent studies have identified the role of miRNAs in neurodegenerative disorders, including AD, PD and Huntington's disease (Maciotta et al, 2013 ; da Silva et al, 2016 ; Salta and De Strooper, 2017 ), changes in the miRNA pattern in developing brain after prenatal hypoxia will certainly result in a neurodegeneration-prone phenotype in later life. Quantitative analysis of hypoxia-regulated miRNAs in the maternal blood may provide a tool for identifying risk of fetal hypoxia (Whitehead et al, 2013 ).…”
Section: Epigenetic Consequences Of Prenatal Hypoxiamentioning
confidence: 99%